Fast vocal-motor tracking of escaping prey in echolocating bats - Ilias Foskolos; Antoniya Hubancheva; Marie Rosenkjær Skalshøi; Kristian Beedholm; Peter Teglberg Madsen; Laura Stidsholt (BMC Biology)
Abstract Background Echolocating bats face an intense arms race with insect prey that can detect bat calls and initiate evasive maneuvers. Their high closing speeds and short biosonar ranges leave bats with only a few 100 ms between detection and capture, suggesting a reactive sensory-motor operation that might preclude tracking of escaping prey. Here we test this hypothesis using greater mouse-eared bats (Myotis myotis) as a model species. With high-resolution biologging tags, we recorded bats hunting aerial prey in the wild and we also collected data from trained conspecifics in the laboratory facing simulated prey escapes of various speeds and distances. Results We show that wild bats employed flexible buzz durations during hunting. In the laboratory, such dynamic vocal responses were driven by moving targets, where faster and longer movements led to longer buzzes. During these buzzes, the bats engaged in acute vocal-motor tracking via increased call intervals within 240 ms of evasive prey maneuvers. Conclusions Echolocating bats can track evasive prey via a fast vocal-motor feedback loop allowing them to expand their acoustic depth of field. This echo-guided sensory adjustment contributes to the hunting superiority of bats as the most formidable insectivorous predator of the night skies.